2016
DOI: 10.1080/21655979.2016.1228497
|View full text |Cite
|
Sign up to set email alerts
|

Ex vivo comparative study on three sinus lift tools for transcrestal detaching maxillary sinus mucosa

Abstract: The objective of this study was to comparatively evaluate 3 different sinus lift tools, namely umbrella-shaped sinus lift curette YSL-04, our recently designed probe-improved sinus lift curettes, and our newly invented elevator 014, using our previous developed goat ex vivo models for direct visualizing the effectiveness of detaching sinus mucosa in real time. Goat ex vivo models for direct visualizing the effectiveness of detaching sinus mucosa in real time were generated according to our previously developed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Several studies of the influence of different types of elevators on t‐SFA have indeed shown the important role of elevator design 25 . Furthermore, when the influence of PIL and GH was analyzed, it showed a linear correlation, suggesting the ability of the protruding part of the implant to assist in graft stabilization.…”
Section: Discussionmentioning
confidence: 91%
“…Several studies of the influence of different types of elevators on t‐SFA have indeed shown the important role of elevator design 25 . Furthermore, when the influence of PIL and GH was analyzed, it showed a linear correlation, suggesting the ability of the protruding part of the implant to assist in graft stabilization.…”
Section: Discussionmentioning
confidence: 91%
“…8,13,14 Recently, we have been designing novel tools for better detaching the maxillary sinus mucosa. 15,16 Ex vivo animal models with the capability of real-time direct visualization have great advantages in the evaluation of the effectiveness of improved or newly designed tools. 17,18 Selection of the proper animal model is crucial to evaluating novel technologies and new materials designed for clinical applications.…”
mentioning
confidence: 99%